2018
DOI: 10.1007/s40266-018-0578-7
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Objectively Measured Physical Activity and Opioid, Hypnotic, or Anticholinergic Medication Use in Older People: Data from the Physical Activity Cohort Scotland Study

Abstract: Anticholinergic burden is associated with greater decline in objectively measured physical activity over time in older people, a finding not seen with hypnotic or opioid use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…Although baseline cognitive function measured by 3MSE was not different between ACB groupings, previous studies have found that anticholinergic medications were associated with worse balance and more falls [18]. This has been speculated to occur due to a reduction in processing speed and promotion of cerebral vasculopathy and consequent white matter changes [19]. In line with our results, other studies have found that anticholinergic burden is associated with greater decline in objectively measured physical activity over time in older adults [19].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although baseline cognitive function measured by 3MSE was not different between ACB groupings, previous studies have found that anticholinergic medications were associated with worse balance and more falls [18]. This has been speculated to occur due to a reduction in processing speed and promotion of cerebral vasculopathy and consequent white matter changes [19]. In line with our results, other studies have found that anticholinergic burden is associated with greater decline in objectively measured physical activity over time in older adults [19].…”
Section: Discussionsupporting
confidence: 88%
“…This has been speculated to occur due to a reduction in processing speed and promotion of cerebral vasculopathy and consequent white matter changes [19]. In line with our results, other studies have found that anticholinergic burden is associated with greater decline in objectively measured physical activity over time in older adults [19]. Additionally, ACB has been associated with a higher incidence of cardiovascular events, which may also demonstrate declines in mobility [20].…”
Section: Discussionsupporting
confidence: 87%
“…The basic activities most affected by the anticholinergic action were bathing, grooming, dressing, transfers, mobility and stairs use (Lowry et al, 2011). A progressive decrease in global activity measured by accelerometers was also found (Clarke et al, 2018). A dose-response relationship between anticholinergic load and dysfunction has also been described.…”
Section: Discussionmentioning
confidence: 91%